Developing academic skills In blended environments - Balula, Ana (2021)
More teacher-centred in general, Higher Education Institutions are moving towards the incorporation of innovative and interactive practices and programmes, and in the last decades e- and b-learning have increasingly become credible alternatives to traditional modes of teaching and learning, and rethinking their curricula and strategies to incorporate e-approaches and digital technologies. The catalysts for this change thrive on the need to keep pace with other universities and recruiting students. The main goal of this paper is to briefly describe a PhD programme of the University of Aveiro, Portugal, and to put forward some selected blended strategies, namely concerning the use of digital technology to enhance learning and develop academic skills. Even though this paper does not directly address the topic of ESP, best practices described here are multi-disciplinary in nature, and offer insights as regards teaching practices and clues for academic and professional development and research on this topic. Stemming from the definition of ‘academic skills’, several online teaching and learning strategies are described. We therefore focus our paper on three selected strategies, used in this PhD for developing project group-work, writing academic papers and presenting research to peers. We delve on three main academic skills (collaboration, writing and presentation), as they are the basis for meaningful and lifelong learning. These are transferable and extensive and rely on students’ critical thinking and also on their team-work and initiative abilities, requiring them to be effective communicators and negotiators. The PhD programme makes use of blended strategies and digital technology to enhance participants’ learning experiences, sustaining the development of their academic skills. Students are required to participate in, produce and disseminate scientific research. Describing how different academic skills are developed throughout the PhD modules, the present text offers a fresh outlook on digital technology as a means of leveraging students’ academic/research skills, putting forth practices that can be relevant for a wide variety of academic and professional domains. The program described is blended and offered in sequential subjects, allowing students to concentrate on a topic at a time and carry out more in-depth and focused research, integrating individual and collective knowledge. This structure and flexible delivery mode also meet the students’ needs due to their professional obligations, promoting opportunities of continuous lifelong learning. Regarding academic skills, by relying strongly on collaboration, interaction and peer feedback, the PhD fosters autonomous learning and critical thinking, offering students the opportunity to engage in networking and the development of interpersonal skills, which are crucial for their academic future, and closer to what will be expected from them in their professional lives.